Phenology of flower and fruit development in Uncaria gambir Species - JAMSARI JAMSARI; YASWENDRI YASWENDRI; MUSLIAR KASIM (Biodiversitas Journal of Biological Diversity, 2007)
A phenological study with the aim to elucidate flower and fruit development stages in species of Uncaria gambir was conducted in field trial of agricultural faculty of Andalas University-West Sumatra. Observation during flower and fruit organ development was done in eleven inflorescences. Quantitative and descriptive data were collected during one season of flowering time. Phenology of flower and fruit development could be classified in five stages, namely F0 (flower initiation), F1 (small bud scale), F2 (large bud scale), F3 (anthesis, flower opening) and F4 (fruit development). All these events had average completing time in 112 days, and could be detailed as follows: flower initiation stage (F0) took place in 20 days, small scale bud stage (F1) occurred in 27 days, and large scale bud and anthesis stage (F0 and F3) each took place in 5 days, meanwhile fruit development stage (F4=S0) would complete in 53 days. This result should be useful information especially for creating breeding programme in Uncaria gambir species.Key words: Uncaria gambir, phenology, flower development, fruit development.